Enthalpic approach to delineate the interactions of cations of imidazolium-based ionic liquids with molecular solvents - Rai, Gitanjali; Kumar, Anil (Physical Chemistry Chemical Physics, 2011)
We present a systematic investigation on the enthalpic assessment of the interactions operating between the cation and anion of four imidazolium ionic liquids with aqueous and various nonaqueous solvents. Accurate experimental information gathered with the help of an isothermal titration calorimeter at 298.15 K has been analyzed for excess partial molar enthalpy of the ionic liquid, H(IL)(E), in terms of hydrophobic and solvation effects. The variations in the limiting excess partial molar enthalpy of the ionic liquid, H(IL)(E infinity), have been correlated with solvent properties. We have quantified the enthalpic effects due to dissociation of ionic liquids in very dilute solutions and to clathrate formation with the increasing concentration of ionic liquid. A change in enthalpic behavior from endothermic to exothermic is observed on increasing the carbon chain length attached to the imidazolium ring. The solvent reorganization around the cationic species has been unraveled by employing the ionic liquid interaction parameters called as H(IL-IL)(E) deduced from the H(IL)(E) data. The apparent relative molar enthalpy, phi(L), derived from H(IL)(E) data has been examined in the light of the specific ion interaction theory as advanced by Pitzer with accurate results.

Elucidation of ionic interactions in the protic ionic liquid solutions by isothermal titration calorimetry - Rai, Gitanjali; Kumar, Anil (Journal of Physical Chemistry B, 2014)
The strong hydrogen-bonded network noted in protic ionic liquids (PILs) may lead to stronger interactions of the ionic entities of PILs with solvents (water, methanol, ethylene glycol, climethylsulfoxide (DMSO), N,N'-dimethylformamide (DMF)) as compared with those of aprotic ionic liquids (APILs). The PILs used in this work are 1-methylimidazolium tetrafluoroborate, 2-methylpyridinium tetrafluoroborate, and N-methylpyrrolodinium tetrafluoroborate in comparison to 1-butyl-3-methylimidazolium tetrafluoroborate, which is classified as an APIL. In this work, the excess partial molar enthalpy, H-IL(E) obtained from isothermal calorimetric titrations at 298.15 K is used to probe the nature of interactions of the PIL cations with solvent molecules against those present in APIL solvent systems. This work also reports interesting flip-flopping in the thermal behavior of these PIL-solvent systems depending upon the structure of the cationic ring of a PIL. In some cases, these flip-flops are the specific fingerprints for specific PILs in a common solvent environment. The excess partial molar enthalpy at infinite dilution, H-IL(E,infinity), of these PILs bears a critical dependence on the solvent properties. An analysis of relative apparent molar enthalpies, phi(L), of the PIL solutions by the ion interaction model of Pitzer yields important information on ionic interactions of these systems.